Desain Short Course dalam Pembelajaran Bahasa Arab Melalui Keterampilan Berbicara (Maharah al-kalam) - Laili Mas Ulliyah Hasan (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2023)
This study aims to determine the Arabic Speaking Skills (Maharah Al-Kalam) of Students of the Arabic Language Education Department at the College of Arabic Language Studies and Da'wah (STIBADA) at the Great Mosque of Sunan Ampel (MASA) Surabaya. Arabic Speaking Skills (Maharah Al-Kalam) Students of the Arabic Language Education Department at STIBADA MASA Surabaya still experience difficulties in speaking Arabic, especially in the kalam section due to 4 things, namely: 1) Low student motivation in learning Arabic. 2) Lack of mastery of Arabic vocabulary. 3) Lack of understanding of the rules of the Arabic language. 4) Students feel afraid when practicing Arabic with fellow students or lecturers. So that in this study by studying Arabic through Speaking Skills (Maharah al-kalam) with the Short Course design the methods used in learning Arabic are observation, interviews, socialization and training with a humanistic approach and the approach is in the form of short courses (lecture programs of duration short). The implementation of this short course is March - May 2023 with the results of the research, namely an increase in learning Arabic through the Short Course design seen from the results of the pretest and posttest scores.